Pengembangan Pembelajaran di TPQ An-Nur Desa Bekiring Pulung Ponorogo - M. Zainul Muqorrobin; Ahmad Kirom (Social Science Academic, 2023)
This research aims to develop learning at TPQ An-Nur. The method used in this study is ABCD (Asset Based Community Driven-Development) in the form of providing education in the form of methods and strategies for accompanying children in learning and creating a more attractive learning atmosphere for children. There are 4 stages in implementing it, namely Discovery / finding out and exploring the assets owned that have been achieved on a journey. In this Dream Stage, we and our friends analyze and look for input and a way out, provide an activity or offer a program that we can implement, what changes we can make in realizing this dream. In this Design Stage we are going on a journey, namely designing and designing what we think is appropriate to make the program we have designed and start from start to finish. In this Desteny stage, it is the stage of our mentoring activity wheel journey through an evaluation of previous activities. The result of this training is to create a learning atmosphere that is fun and much-loved by children to attract children's desire to study religion at TPQ An Nur, the higher the interest of students in studying.